Differential Identification of Mycobacterium tuberculosis Complex and Nontuberculous Mycobacteria by Duplex PCR Assay Using the RNA Polymerase Gene (rpoB) - Kim, Bum-Joon (American Society for Microbiology, 2004)
A novel duplex PCR method that can amplify the 235- and 136-bp rpoB DNAs of Mycobacterium tuberculosis complex and nontuberculous mycobacteria (NTM), respectively, with two different sets of primers was used to differentially identify 44 reference strains and 379 clinical isolates of mycobacteria in a single-step assay. Showing 100% sensitivity and specificity, the duplex PCR method could clearly differentiate M. tuberculosis complex and NTM strains. In addition, restriction fragment length polymorphism analysis and direct sequencing of the amplicon of NTM could be used to supplement species identification.